Apakah Efek Pandemi Covid-19 Meningkatkan Return Saham Perusahaan Teknologi ? - Yafez Rahmentio; Annisaa Rahman; Defriko Gusma Putra; Riyadi Aprayuda (Jurnal Ecogen, 2022)
This study aims to identify the impact of the covid pandemic on technology company stock returns. In particular, this study will classify the stock returns of technology companies from the beginning to the time the Covid-19 pandemic occurred in Indonesia. This study uses a qualitative descriptive literature study method to describe stock price report data from 28 technology companies in Indonesia which are members of 23 technology companies engaged in software development and information technology services, and 5 technology companies in the hardware and equipment sector. The results of this study indicate that 12 of the 28 companies that are members of the technology sector provide a return of more than 100% within one year. Then, as a result of the policy in dealing with the Covid-19 pandemic, companies engaged in the technology sector have a role as producers and distributors of procurement of equipment and services for the technology industry in creating new communications to support the daily activities of the community and other industrial sector companies. As a practical contribution, this research can be used as a reference for investors as an attractive investment option in their stock portfolio, because since the pandemic this company has been able to generate high profits.